Vector-based 3D graphic statics: A framework for the design of spatial structures based on the relation between form and forces. (1st August 2019) - D'Acunto, Pierluigi; Jasienski, Jean-Philippe; Ohlbrock, Patrick Ole; Fivet, Corentin; Schwartz, Joseph; Zastavni, Denis
Abstract: This article develops a vector-based 3D graphic statics framework that uses synthetic and intuitive graphical means for the analysis and design of spatial structures such as networks of bar elements in static equilibrium. It is intended to support the collaborative work of structural engineers and architects from the conceptual phase of the design process. Several procedures for the construction of a vector-based 3D force diagram for any given 3D form diagram with an underlying planar or non-planar graph are identified and described. In the non-planar case, the proposed procedures rely on the preliminary topological planarization of the graph by cutting the crossing edges and reconnecting them to one or more newly inserted auxiliary vertices. Resulting planar graphs can be then used as a base for the assembly of 3D force diagrams, without altering the static equilibrium of the structure. An implementation of the proposed framework to real design scenarios is presented through two case studies. These examples demonstrate the benefits of bi-directional manipulations of form and force diagrams in the structural design process.